Understanding the Association between Personality Traits and Motivational Potential of Jobs - The Employees’ Perspective - Bajwa, Ruqia Safdar; Batool , Iram; Shahid , Muhammad Sadiq (South Asian Journal of Social Sciences and Humanities, 2021)
Interaction between human personality, traits and behaviors at work has already been studied.  Existing literature increasingly highlights the importance of the relationship between personality  traits and job characteristics. This study particularly explored the relationship between employees’ personality traits and potential motivational factors at work. For this purpose, a  sample of 184 employees was selected from various organizations of Multan City. Five Factor  inventory and job diagnostic survey scale was used to measure study variables. The findings  indicated that traits of personality like extroversion, openness to experience, agreeableness and  conscientiousness are positively associated, whereas neuroticism is negatively associated with the  perceived motivational potential of jobs. Furthermore, the motivational potential of jobs is found  to vary across the organizations; females are found to perceive their jobs more motivating as  compared to males; and the job characteristics of autonomy and skill variety have been found  positively related with the personality trait of openness to experience and negatively correlated  with the personality trait of neuroticism. By matching core job characteristics and personality traits at the time of recruitment can be highly beneficial for best selection of employees, productivity and different outcomes related to employee’s performance.
Keywords: Employees’ personality traits; Motivational potential of jobs; Job characteristics; Big Five personality traits